Creativity & innovation : theory, research, and practice - Plucker, Jonathan A., 1969- (Prufrock Press Inc., 2017)
Creativity and innovation are frequently mentioned as key 21st-century skills for career and life success. Indeed, recent research provides evidence that the jobs of the future will increasingly require the ability to bring creative solutions to complex problems.